Analysis of the Effect of the Family Hope Program (PKH) in Alleviating Poverty in Seberang Teluk Hilir Village, Kuantan Tengah District, Kuantan Regency - Rahmita Budiartiningsih; Selly Prima Desweni; Bunga Chintia Utami; Ando Fahda Aulia; Nobel Aqualdo (Universitas Teuku Umar, 2022)
This research is based on implementing the Hope Family Program (HFP) as an alternative policy in reducing poverty in Indonesia, including Seberang Taluk Hilir Village, Central Kuantan District, Kuantan Singingi Regency. This study's problem formulations and objectives are: 1) how is the influence of HFP in overcoming poverty in Seberang Taluk Hilir Village, 2) the extent of the influence of the HFP program in overcoming poverty in Seberang Taluk Hilir Village. The population and samples of this study was 50 households who received direct assistance. This research is using Qualitative method with non-experimental.Data collection was carried out through observation, in-depth interviews and documentation. The data analysis technique uses an interactive model through data reduction, data presentation, and conclusion drawing.The results showed a very big influence with the HFP program for the survival of the beneficiary, a change in consumption patterns and the ability to meet their daily needs. The achievement of the HFP program objectives for household recipients of assistance, especially in terms of education and health are getting better. Strengthened by management and supervision by household facilitators so that beneficiary communities can manage cash assistance properly.There needs to be a government policy to improve service quality, especially the number of HFP facilitators who are still lacking, so that the role of the assistants is still not maximal in serving and supervising the implementation of the HFP program in the village of Seberang Taluk Hilir